(untitled) (Journal of Medicine, 2014)
The aim of the study was to assess the association of metabolic syndrome in patients with acute coronary syndrome and the impact of metabolic syndrome on clinical outcome. Total 210 ACS patients were included in this study and divided in group I & II on the basis of presence or absence of MS respectively. Among the study patients mean age in group I and group II was 52.99 ± 11.49 years and 53.34 ± 12.54 years respectively. Among the risk factors, hypertension (70%vs 15%), dyslipidemia (100 vs. 97%), diabetes mellitus (36.4% vs. 6%) were significant between two groups. Mean waist circumference recorded was 103.12 ± 4.15 in group I and 96.50 ± 6.43 in group II which was significant. Present study showed, in hospital outcome was worse in group I in comparison to group II and was significant, like cardiogenic shock (11% vs. 1%), LVF (28.2% vs. 16%), and CVD (5.45 vs. 0%). But there were no significant difference in heart block, tachyarrhythmia, cardiac arrest, reinfarction and death. Complications were far more in group I than in group II (14.5% vs. 52.0%) which was also highly significant. So, we conclude that the presence of MS in patients suffered from ACS was associated with a greater incidence of in-hospital cardiovascular complications and mortality. DOI: http://dx.doi.org/10.3329/jom.v15i1.19857 J Medicine 2014; 15: 31-35